Socioeconomic status overrides age and gender in determining health-seeking behaviour in rural Bangladesh - Syed Masud Ahmed; Göran Tomson; Max Petzold; Zarina Nahar Kabir (The World Health Organization, 2005)
OBJECTIVE: To study the health-seeking behaviour of elderly members (aged > 60 years) of households in rural Bangladesh, to ascertain how their behaviour differs from that of younger people (aged 20-59 years) living in the same household and to explore the determinants of health-seeking behaviour. METHODS: Structured interviews were conducted to elicit information on the health-seeking behaviour of household members aged > 20 years. Respondents were asked about major illnesses occurring within 15 days prior to the interview. The sample consisted of 966 households that had at least one resident who was aged > 60 (32% of 3031 households). FINDINGS: We found no major differences in health-seeking behaviour between elderly people and younger adults. On average about 35% (405/1169) of those who reported having been ill during the previous 15 days in both age groups chose self-care/self-treatment; for both age groups the most commonly consulted type of provider was a paraprofessional such as a village doctor, a medical assistant or a community health worker. A household's poverty status emerged as a major determinant of health-seeking behaviour. The odds ratio (OR) that individuals from poor households would seek treatment from unqualified allopathic practitioners was 0.6 (95% confidence interval (CI) = 0.40-0.78); the odds ratio that individuals from poor households would seek treatment from qualified allopathic practitioners was 0.7 (95% CI = 0.60-0.95). For self-care or self-treatment it was 1.8 (95% CI = 1.43-2.36). Patients' level of education affected whether they avoided self-care/self-treatment and drugstore salespeople (who are usually unlicensed and untrained but who diagnose illnesses and sell medicine) and instead chose a formal allopathic practitioner (OR = 1.5; 95% CI = 1.15-1.96). When a household's poverty status was controlled for, there were no differences in age or gender in terms of health-care expenditure. CONCLUSION: We found that socioeconomic indicators were the single most pervasive determinant of health-seeking behaviour among the study population, overriding age and sex, and in case of health-care expenditure, types of illness as well.